2020
DOI: 10.1101/2020.05.11.086017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Huntington’s disease-specific mis-splicing captured by human-mouse intersect-RNA-seq unveils pathogenic effectors and reduced splicing factors

Abstract: Deregulated alternative splicing has been implicated in a wide range of pathologies. Deep RNAsequencing has revealed global mis-splicing signatures in multiple human diseases; however, for neurodegenerative diseases, these analyses are intrinsically hampered by neuronal loss and neuroinflammation in post-mortem brains. To infer splicing alterations relevant to Huntington's disease (HD) pathogenesis, here we performed intersect-RNA-seq analyses of human postmortem striatal tissue and of an early symptomatic mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…brain, muscle), usually through the action of tissue-enriched alternative splicing factors, and are known to play crucial roles in cellular differentiation and physiology [33, 34]. Moreover, some sets of exons have been shown to be jointly mis-regulated in human pathologies, including cancer or mental disorders [35, 36], and the evolutionary comparison between human and model organisms is a powerful approach to identify potential pathogenic targets [37]. The ExOrthist compare_exon_sets module allows the evaluation of the evolutionary conservation of exon sets between two species from a genomic and regulatory perspective, both at the gene and exon level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…brain, muscle), usually through the action of tissue-enriched alternative splicing factors, and are known to play crucial roles in cellular differentiation and physiology [33, 34]. Moreover, some sets of exons have been shown to be jointly mis-regulated in human pathologies, including cancer or mental disorders [35, 36], and the evolutionary comparison between human and model organisms is a powerful approach to identify potential pathogenic targets [37]. The ExOrthist compare_exon_sets module allows the evaluation of the evolutionary conservation of exon sets between two species from a genomic and regulatory perspective, both at the gene and exon level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since P2X7R protein levels are augmented in HD striatum, we investigated whether this increase is associated with a higher amount of total P2X7R transcript in this brain area. To achieve such aim, we analyzed an RNA-seq study of the striatum of HD patients and controls that we have recently performed ( Elorza et al, 2020 ). We found a strong increase in total P2X7R transcript level (2.4-fold, q = 0.005) in HD subjects ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…P2X7R expression levels in HD and CTRL postmortem striatum samples were evaluated from our RNA-seq data (CTRL = 3 vs. HD = 3) ( Elorza et al, 2020 ). For total mRNA transcript levels, reads were aligned against the Homo sapiens genome (GRCh38.p2 version) using the TopHat2 aligner ( Trapnell et al, 2009 ), and differentially expressed genes were obtained with the Cuffdiff software ( Trapnell et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in a recent study, Elorza et al performed intersect-RNA-seq analyses of human postmortem striatal tissue and of an early symptomatic mouse model in which neuronal loss and gliosis were not yet present. This, in combination with a human–mouse parallel motif scan analysis, allowed for the identification of a shared mis-splicing signature that was triggered by the CAG-repeat mutation in both species and gives rise to a total of 949 one-to-one orthologs that are differentially spliced in both human and mouse [ 61 ]. In addition, via human–mouse parallel complementary motif searches on common mis-spliced events, the authors concluded a network of candidate upstream splicing factors with reduced protein levels in both species that may be mechanistically involved in mis-splicing [ 61 ].…”
Section: Deregulated Splicingmentioning
confidence: 99%
“…This, in combination with a human–mouse parallel motif scan analysis, allowed for the identification of a shared mis-splicing signature that was triggered by the CAG-repeat mutation in both species and gives rise to a total of 949 one-to-one orthologs that are differentially spliced in both human and mouse [ 61 ]. In addition, via human–mouse parallel complementary motif searches on common mis-spliced events, the authors concluded a network of candidate upstream splicing factors with reduced protein levels in both species that may be mechanistically involved in mis-splicing [ 61 ]. Interestingly, some of these splicing factors, for example, U2AF2 and HNRNPC, were previously found to aberrantly bind to CAG-repeat RNA [ 52 ].…”
Section: Deregulated Splicingmentioning
confidence: 99%